The Impact of DevOps on Software Development and IT Operations (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article examines the perspectives of industry experts on the influence of DevOps on software development and IT operations, as well as alternative models for its implementation. It explores the benefits, challenges, and future trends of DevOps adoption in the software industry.